Characterization of lake water-groundwater exchange at Lake L5, Universiti Teknologi PETRONAS, Malaysia - Orji, K.U. (WITPress, 2013)
Mining lakes are rarely used in Malaysia for raw water supply in water treatment despite their abundance. This is based on the general view that they are just mere retention ponds. However, there is growing acknowledgement that surface water features such as rivers and lakes can exchange water with underlying aquifers and this water movement can have significant implications on water quantity. This study examined the interaction between surface water (mining lake water) and groundwater (aquifer) using Lake L5 at the Universiti Teknologi PETRONAS, Perak, Malaysia, as a case study. Seepage meters and mini piezometers were used to evaluate the seepage flux rates, direction, and magnitude of water flow between the aquifer and the lake water. The seepage flux rates were found to be in the range of 3.45 Lm-2day-1 to 11.08 Lm-2day-1 and the Vertical Hydraulic Gradients (VHG) of the mini piezometers was within the range of 0.022 to 0.196. The results from these methods were positive, correlated and confirmed that groundwater was being discharge into the lake water; and that the farther the monitoring equipment from the shoreline, the lesser the groundwater discharge. Further research is required to be carried out for a longer period, under different hydrological conditions and time of the year, and at several locations. Â© 2013 WIT Press.